2003
DOI: 10.1007/bf02504518
|View full text |Cite
|
Sign up to set email alerts
|

Integrating technology in a field-based teacher training program: The PT3@ASU project

Abstract: The Preparing Tomorrow's Teachers to Use Technology (PT3) initiative has funded various efforts to improve and enhance the technology preparation of preservice teachers. At Arizona State University, these efforts have focused on providing preservice teachers with opportunities to develop, implement, and evaluate their own instructional activities that utilize technology effectively and appropriately in authentic situations, to give them the myriad of tools necessary to integrate technology into teaching and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
8

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(88 citation statements)
references
References 16 publications
2
78
0
8
Order By: Relevance
“…actual classroom use, as there are still reports of limited access to technology (e.g., Bartlett, 2002;Brush et al, 2003;Russell et al, 2003).…”
Section: Teachers Perceptions Of Web-based Learning Tools 28mentioning
confidence: 99%
“…actual classroom use, as there are still reports of limited access to technology (e.g., Bartlett, 2002;Brush et al, 2003;Russell et al, 2003).…”
Section: Teachers Perceptions Of Web-based Learning Tools 28mentioning
confidence: 99%
“…Educators face a number of challenges when attempting to use technology in their classrooms including the amount of time required (Eifler, Greene, & Carroll, 2001;Wepner, Ziomek, & T ao, 2003), having to work with limited technological skills (Eifler et al, 2001;Strudler, Archambault, Bendixen, Anderson, & Weiss, 2003;T hompson, Schmidt, & Davis, 2003), fear of technology (Bullock, 2004;Doering, Hughes, & Huffman., 2003), difficulty in understanding how to integrate technology into teaching (Cuban, 2001), and insufficient access (Bartlett, 2002;Brush et al, 2003;Russell et al, 2003).…”
Section: Potential For Using Learning Objects In Secondary Schoolmentioning
confidence: 99%
“…Teacher educators have reported successful methodologies for instructing pre-service teachers about ICT integration practices even before the conceptualization of TPACK (e.g. Brush et al, 2003). Their influences on teachers' TPACK, if examined thoroughly, can potentially enrich the practical use of the TPACK framework towards teacher ICT development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Before the conception of TPACK, a considerable number of studies have discussed programme-wide strategies to strengthen teachers' confidence in ICT integration. These studies largely concluded the need for teacher education curricula to provide pervasive faculty modelling of technology integration practices, hands-on ICT lesson design activities, and ICT field-based practicum (Brush, et al, 2003;Handler, 1993;Strudler & Wetzel, 1999). The TPACK framework extends these studies because it suggests a theoretical basis for teacher educators to measure the outcomes of ICT courses, which, in earlier studies were largely centred upon building teachers' confidence for ICT integration.…”
Section: Tpack-fostering Instructional Processesmentioning
confidence: 99%